2017
DOI: 10.3389/fnins.2017.00558
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Activates AMPK Pathway and Regulates Lipid Metabolism in Rats Following Prolonged Clozapine Exposure

Abstract: Clozapine (CLO) remains an ultimate option for patients with treatment resistant schizophrenia. However, the atypical antipsychotic is often associated with serious metabolic side effects, such as dyslipidemia. Hepatic sterol regulatory element-binding proteins (SREBPs) are central in the allosteric control of a variety of lipid biosynthetic pathways. There is emerging evidence that CLO can activate SREBP pathway and enhance downstream lipogenesis, whereas curcumin (CUR), a major active compound of Curcuma lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…Curcumin, a dietary bio-active derived from turmeric, has been shown to alleviate insulin resistance and lower fasting glucose in preclinical studies 5 7 . These effects were hypothesised to be mediated via lowering of low grade inflammation via down-regulation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) 8 , cytoprotection of pancreatic β-cells by increasing the concentrations of anti-oxidant enzymes 9 and via increasing expression of 5′ adenosine monophosphate-activated protein kinase (AMPK) 10 , a key regulator of glucose and lipid homeostasis. Clinical trials with curcumin supplementation reported positive 11 and no effect 12 on fasting glycaemic parameters in high risk and individuals with type 2 diabetes 13 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, a dietary bio-active derived from turmeric, has been shown to alleviate insulin resistance and lower fasting glucose in preclinical studies 5 7 . These effects were hypothesised to be mediated via lowering of low grade inflammation via down-regulation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) 8 , cytoprotection of pancreatic β-cells by increasing the concentrations of anti-oxidant enzymes 9 and via increasing expression of 5′ adenosine monophosphate-activated protein kinase (AMPK) 10 , a key regulator of glucose and lipid homeostasis. Clinical trials with curcumin supplementation reported positive 11 and no effect 12 on fasting glycaemic parameters in high risk and individuals with type 2 diabetes 13 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have described various effects of curcumin including reducing blood fat, choleretic actions, and antitumor, anti-inflammatory, and anti-oxidation effects [13][14][15][16] . Several studies have indicated that the effect of curcumin on SREBPs is related to the mechanism of curcumin regulating blood lipid metabolism [4,5,[8][9][10][11][12] . Kumar et al [4] found that curcumin can regulate the expression of NPC1L1 through SREBP-2 to inhibit cholesterol absorption in Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the detected protein may be mSREBP-2 rather than pSREBP-2. Liu et al [10] studied the function of curcumin using antibodies against SREBP-2 purchased from Santa Cruz which have only been used to detect pSREBP-2. Our results indicate that curcumin first affects the SREBP-2 proteolysis process rather than inhibiting its protein expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations